Characterization of the chloroplast genome of a rare species in China, Lilium martagon var. pilosiusculum. Issue 1 (2nd January 2018) - Zhou, Yanping; Bi, Yu; Yan, Qiheng; Jia, Guixia; Du, Yunpeng
Abstract: Lilium martagon var. pilosiusculum is an endangered species with high ornamental value in Xinjiang province (China). In this study, we reported a complete chloroplast genome of L. martagon var. pilosiusculum, which was de novo assembled using the next-generation sequencing data. The complete chloroplast genome is 152, 816 in length, including a large single copy region of 82, 265 bp and a small single copy region of 17, 541 bp and two inverted repeat regions of 26, 505 bp. A total of 110 functional genes were encoded, consisting of 76 protein-coding genes, 30 transfer RNA genes, and four ribosomal RNA genes. The overall AT content of the chloroplast genome is 63.00%. In addition, 68 SSRs and 31 large repeat sequences were found. In the maximum likelihood tree, a strong phylogenetic signal showed that L. martagon var. pilosiusculum is a species of lilium .